Ammonia oxidisers in a non-nitrifying Brazilian savanna soil. Issue 11 (21st September 2017) - Catão, Elisa C P; Thion, Cécile; Krüger, R.H.; Prosser, James I
Abstract: Low nitrification rates in Brazilian savanna (Cerrado) soils have puzzled researchers for decades. Potential mechanisms include biological inhibitors, low pH, low microbial abundance and low soil moisture content, which hinders microbial activity, including ammonia oxidation. Two approaches were used to evaluate these potential mechanisms: (i) manipulation of soil moisture and pH in microcosms containing Cerrado soil and (ii) assessment of nitrification inhibition in slurries containing mixtures of Cerrado soil and an actively nitrifying agricultural soil. Despite high ammonium concentration in Cerrado soil microcosms, little NO3 − accumulation was observed with increasing moisture or pH, but in some Cerrado soil slurries, ammonia-oxidising archaea (AOA) amoA transcripts were detected after 14 days. In mixed soil slurries, the final NO3 − concentration reflected the initial proportions of agricultural and Cerrado soils in the mixture, providing no evidence of nitrification inhibitors in Cerrado soil. AOA community denaturing gradient gel electrophoresis profiles were similar in the mixed and nitrifying soils. These results suggest that nitrification in Cerrado soils is not constrained by water availability, ammonium availability, low pH or biological inhibitors, and alternative potential explanations for low nitrification levels are discussed. Abstract : Despite the presence of ammonia oxidiser microbial communities, Brazilian savanna soils rarely nitrify which can be regarded as an ecological advantage to retain N in soil.